Inserção da agenda etnico- racial na política de desenvolvimento territorial e a inclusão produtiva de comunidades quilombolas - Vieira, Lucas Moretz-Sohn David (2018)
From the recognition of the extreme ethnic and racial inequality in Brazil, the study aimed at discussing the integration of ethnic-racial “agenda” in the Rural Development Policy with a territorial approach. Using Sociology of Public Action as theoretical frame, the implementation of “Programa de Desenvolvimento Sustentavel de Territorios Rurais (PRONAT) in the “Centro Serra” territory and its impact to the “Comunidade Quilombola Linha Fão” (municipality of Arroio do Tigre) was analyzed for 2009/2017. Suggested analytical categories of the Public Policies Pentagon (actors, representations, institutions, processes and results) were used to guide the analysis of the policy implementation. The analyses were carried out based on a review of the scientific literature produced on the theme (for contextualization of ethnic-racial “agenda”, characterizes territorial development policy and the historical trajectory of “Centro Serra” social configuration), analysis of PRONAT normative documents, the mitnutes of CODETER meetings, participant observation and semi-structured interviews with “quilombola” community members. As research results, it was observed that the territorial development public policy, by itself, does not guarantee the productive inclusion of “Quilombola” communities and that, even with the resource being accessed, did not generate much expectation in the community regarding its execution. It is considered that due to brazilian territorial policy origins (with a family farm orientation) and given the high bureaucratic requirement for the submission of proposals, there is limited opportunity to Quilombola community agency in this process. The territory history, characterized by a continuous expropriation of lands of the most vulnerable groups, made them search and adopt livelihoods other than those recommended by the territorial policy.